Analisis Dan Perancangan Sistem Informasi Pemesanan Dan Penjualan Pakaian Muslim Berbasis Web Pada Toko Hidayatullah Jambi - Effendy, Effendy; Mulyono, Herry (LPPM Universitas Dinamika Bangsa, 2020)
Hidayatullah store is a store that is engaged in the business of selling Muslim clothing and other goods nuanced Muslims. In Hidayatullah Toko business processes currently running on the whole done manually which sales promotion from one person to another and advertising. In other words, the business processes that are running do with the media using direct interaction with customers, especially in the promotion, booking and sales. Of these problems the author tries to analyze and design a marketing information system and web-based Muslim apparel sales in stores Hidayatullah using system modeling method UML (Unified Modeling Language) includes Use Case diagrams, activity diagrams, and Class Diagrams. Results from this study is an analysis of sales and marketing information systems web-based Muslim dress in the show in the form of a prototype. As well as the expected future analsisis and design of this system can diimpelentasikan.